Expressions of glutathione S-transferase alpha, mu, and pi in brains of medically intractable epileptic patients - Shang, Wei (BioMed Central, 2008)
BACKGROUND: Glutathione S-transferases (GSTs) play an important role in metabolizing anti-epileptic drugs (AEDs) in liver. Expressions of GSTs in brain, which may result in poor efficacy of AEDs, have not been well studied. Using clinical cortex specimen from 32 intractable epileptic subjects and 8 non-epileptic controls, the present study investigated the correlation between GSTs and intractable epilepsy. RESULTS: Three different GST isoforms (α, μ, and π) were detected with immunohistochemistry. GST-α expression was not seen in any cortex specimens. Sixty three percent (63%) of control and 53% of intractible epileptic specimens showed GST-μ immunoreactivity. No significant difference in intensity of GST-μ staining was observed between these two groups. GST-π expression was found in endothelial cells and glial cells/astrocytes. Fifty percent (50%) of the control patients and 66% of the epileptic patients were GST-π positive. The grading of epileptic patients was significantly higher than that of control patients (p < 0.01). CONCLUSION: High levels of GST-π in endothelial cells and glial cells/astrocyte correlate to medical intractable epilepsy, suggesting that GST-π contributes to resistance to AED treatment.